ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPA-BIOLOGI KELAS VIII-B DI SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO - Buulolo, Angela Rohani (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
Based on the background of the problem, the learning process is still based on the teacher and does not involve complete student participation, students mostly listen and write what the teacher conveys during the learning process. Student activity seems to be lacking in the learning process, especially student activity in asking/confirming with the teacher regarding the material discussed and the subject teacher. Teachers do not fully understand the learning difficulties of students in Class VIII-B at SMP Negeri 1 Luahagundre Maniamolo. This research aims to be descriptive qualitative. The research results show that students experience learning difficulties in the Biology science subject. This research data was analyzed using interview, documentation and informant methods. The results of this research are that there are student learning difficulties. Internal factors that cause students' learning difficulties are intelligence, interests and talents, learning media. Meanwhile, external factors that cause students to experience learning difficulties are the school environment, parents and the community environment. The researcher's suggestions (1) teachers should be able to better control the class during the learning process, and apply good learning and provide conclusions from students' questions. (2) Future researchers should carry out this research with a wider scope.